Essai sur la cryptographie du symbolisme ksourien - Belhedi, Habib; Zecchini, Marino (Le Sahara et l'homme: un savoir pour un savoir faire, 2006)
Keywords: Attushi, mosquée al- (Wersighen, Djerba); Monuments -- Djerba

Some aspects of the vegetation of Dhofar (Southern Oman) - Tardelli, Marcello; Raffaelli, Mauro (Proceedings of the VI Conferenc on Plant Taxonomy: Alghero, 31 May - 2 June 2003, 2006)
Keywords: Botanique -- Oman

Phytogeographic zones of Dhofar (Southern Oman) - Raffaelli, Mauro; Tardelli, Marcello (Proceedings of the VI Conferenc on Plant Taxonomy: Alghero, 31 May - 2 June 2003, 2006)
Keywords: Botanique -- Oman

La rinascita dell'attività politica in Tripolitania nel secondo dopoguerra secondo alcuni documenti britannici (dicembre 1945-gennaio 1949) - Cresti, Federico (La Libia tra Mediterraneo e mondo islamico: atti del convegno di Catania, La Libia tra Mediterraneo e mondo islamico, studi e tendenze della ricerca sulla Libia contemporanea, storia e società, Catania, Facoltà di scienze politiche, 1-2 dicembre 2000: aggiornamenti e approfondimenti, 2006)

L'homonymie maqâmique, redondance ou singularité - Gouja, Mohamed (Paroles d'artistes, 2006)
Keywords: Musique

Pourquoi une théorie de la musique, cas de la musique arabe: problèmes épistémologiques et méthodologiques, enclavements théoriques et conceptuels - Gouja, Mohamed (De la théorie à l'art de l'improvisation: analyse de performances et modélisation musicale, 2006)
Keywords: Musique

إطار العلاقات العمانية المصرية المعاصرة - رزق, يونان لبيب (حوارات صالون الفراهيدي, 2006)
Keywords: Relations -- Oman -- Egypte

ملامح العلاقات المصرية العمانية في التاريخ الحديث - عرب, محمد صابر (حوارات صالون الفراهيدي, 2006)
Keywords: Relations -- Oman -- Egypte

جذور العلاقات التاريخية بين مصر وعمان - عبد الحليم, رجب محمد (حوارات صالون الفراهيدي, 2006)
Keywords: Relations -- Oman -- Egypte

نشأة المدائح النبوية في الشعر العماني - درويش, أحمد (حوارات صالون الفراهيدي, 2006)
Keywords: Poésie -- Oman

ماذا بعد موسوعة السلطان قابوس لأسماء العرب؟ - شوشة, فاروق (حوارات صالون الفراهيدي, 2006)

الأبعاد الثقافية لأسماء العرب - حجازى, محمود فهمي (حوارات صالون الفراهيدي, 2006)

الدلالات الاجتماعية لاسماء العرب - هلال, على الدين (حوارات صالون الفراهيدي, 2006)

السلطان قابوس لاسماء العرب - البوسعيدي, عبد الله بن حمد (حوارات صالون الفراهيدي, 2006)

قصيدة - البوسعيدي, عبد الله بن حمد (حوارات صالون الفراهيدي, 2006)
Keywords: Poésie -- Oman

المنظومة اللغوية عند الخليل بن أحمد - عفيفي, أحمد (حوارات صالون الفراهيدي, 2006)

عبقرية الخليل بن أحمد في استنباط العروض - عبد اللطيف, محمد حماسة (حوارات صالون الفراهيدي, 2006)

الجامع الرياضي لمفردات اللغة العربية عند خليل بن أحمد - بدي, السعيد (حوارات صالون الفراهيدي, 2006)

كتاب العين الخليل بن أحمد وموقعه في آثار الدارسين - بشر, كمال (حوارات صالون الفراهيدي, 2006)

Aterians in Libya - Garcea, Elena (Sessions générales et posters, section 15, préhistoire en Afrique : actes du XIVème congrès UISPP, Université de Liège, Belgique, 2 - 8 septembre 2001, 2006)
Le but de cet article est de démontrer l'existence d'horizons atériens chronologiquement,echnologiquement et typologiquement différents, qui représentent divers groupes culturels adaptés àconditions de milieu variées dans la Libye septentrionale et méridionale. Bien que certaines techniques et outillages communs appairassent sur un territoire étendu, ils sont séparés par de dizaines de millénaires. Il est probable que les populations atériennese sont organisées socialement de manière isolée. Un tel système pourrait expliquer la longue durée des traditions technologiques du MSA ancien à I'Atérien nord-african tardif et pourrait justifier leur diffirsion à un rythme très lent sur ce vaste territoire
Keywords: Géologie -- Djebel Nefousa

In His (Arab) Majesty's Service : The Career of a Somali Scholar and Diplomat in Nineteenth-Century Zanzibar - Hoffman, Valerie J. (The global worlds of the Swahili: interfaces of Islam, identity and space in 19th and 20th century East Africa, 2006)
Keywords: Zanzibar

La chaussée d’al-Qanṭara, pont entre Djerba et le continent - Prevost, Virginie (Autour de la géographie orientale... et au-delà: en l'honneur de J. Thiry, 2006)

Contestations identitaires et politiques en Algérie (1945-1980). Le poids du local - Salhi, Mohamed Brahim (Être notable au Maghreb, 2006)
Pp. 265-270: the example of Reformism in the Ibāḍī environment of Mīzāb is illustrative of a movement that in pursuit of disrupting the old social order, while accompanying and giving form to economic modernization, reaches a compromise in preserving the essential principles that constitute the essence of that environment (Berber-Ibāḍī community in the chebka of Mīzāb).

al-Shaykh Aḥmad b. Sulaymān b. al-Naḍr al-Samā’ilī: ʿAṣruhu, Sīratuhu, mā waṣala ilaynā min Āthārihi - Salīmī, Maḥmūd b. Mubārak al- (Qirā’āt fī Fikr Aḥmad b. Sulaymān b. al-Naḍr al-Samā’ilī. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī Yawmay 27-28 Muḥarram 1424 al-muwāfiq 30-31 Māris 2003, 2006)
Keywords: Biographies -- Oman

Shurūḥāt al-Daʿā’im li-Ibn al-Naḍr min Wujhat Naẓr Tārīkhiyya - Salimi, Abdulrahman al- (Qirā’āt fī Fikr Aḥmad b. Sulaymān b. al-Naḍr al-Samā’ilī. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī Yawmay 27-28 Muḥarram 1424 al-muwāfiq 30-31 Māris 2003, 2006)

al-ʿAllāma Ibn al-Naḍr wa-Shiʿruhu fī ‘l-Daʿā’im - Nājī, Majīd ʿAbd al-Ḥamīd (Qirā’āt fī Fikr Aḥmad b. Sulaymān b. al-Naḍr al-Samā’ilī. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī Yawmay 27-28 Muḥarram 1424 al-muwāfiq 30-31 Māris 2003, 2006)
Keywords: Poésie -- Oman

Muḥāḍara fī Fiqh al-ʿAllāma Ibn al-Naḍr - Khalīlī, Aḥmad b. Ḥamad al- (Qirā’āt fī Fikr Aḥmad b. Sulaymān b. al-Naḍr al-Samā’ilī. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī Yawmay 27-28 Muḥarram 1424 al-muwāfiq 30-31 Māris 2003, 2006)
Keywords: Fiqh

Kitāb al-Daʿā’im: Dirāsa Muqārana - Ḥārithī, Khalfān b. Muḥammad b. ʿAbdallāh al- (Qirā’āt fī Fikr Aḥmad b. Sulaymān b. al-Naḍr al-Samā’ilī. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī Yawmay 27-28 Muḥarram 1424 al-muwāfiq 30-31 Māris 2003, 2006)

Contemporary poetry in Oman - Michalak-Pikulska, Barbara (Modern Oman: studies on politics, economy, environment and culture of the Sultanate, 2006)
Keywords: Littérature -- Oman

Population and workforce in Oman - Kapiszewski, Andrzej (Modern Oman: studies on politics, economy, environment and culture of the Sultanate, 2006)

Oman’s economic development - Pikulski, Andrzej (Modern Oman: studies on politics, economy, environment and culture of the Sultanate, 2006)

Study groups, gender and the tradition of knowledge in Bahla - Limbert, Mandana E. (Modern Oman: studies on politics, economy, environment and culture of the Sultanate, 2006)

Adopting to biodiversity conservation: the mobile pastoral Harasis tribe in Oman - Chatty, Dawn (Modern Oman: studies on politics, economy, environment and culture of the Sultanate, 2006)

Majlis al-Shura in Oman - Salimi, Hussain S. al- (Modern Oman: studies on politics, economy, environment and culture of the Sultanate, 2006)
Keywords: Vie politique -- Oman -- 1970-2020

Broadening political participation in Oman. Basic facts - Kapiszewski, Andrzej (Modern Oman: studies on politics, economy, environment and culture of the Sultanate, 2006)
Keywords: Vie politique -- Oman -- 1970-2020

Oman under Qaboos: the emergence of a new diplomatic style in the Gulf - Rabi, Uzi (Modern Oman: studies on politics, economy, environment and culture of the Sultanate, 2006)
Keywords: Vie politique -- Oman -- 1970-2020

Oman, Pakistan and Gwadur 1948-1958 - Hedigan, Christopher (Modern Oman: studies on politics, economy, environment and culture of the Sultanate, 2006)

British travellers in Oman from 1627- to 1970 - Hajri, Hilal al- (Modern Oman: studies on politics, economy, environment and culture of the Sultanate, 2006)
Keywords: Récits de voyage -- Oman

The territorial divisions of Oman - Wilkinson, John Craven (Modern Oman: studies on politics, economy, environment and culture of the Sultanate, 2006)
Keywords: Vie politique -- Oman

الخوارج النجدات وأثرهم السياسي في العصر الأموي - الشريف, عبدالله بن حسين الشنبري (مداولات اللقاء العلمي السنوي السابع: دول مجلس التعاون لدول الخليج العربية عبر العصور, 2006)
Keywords: Kharijisme

Abd Allah ibn Ibâd and the Origins of the Ibâdiyya - Madelung, Wilferd (Authority, privacy and public order in Islam: proceedings of the 22nd Congress of L'Union européenne des arabisants et islamisants, 2006)

Proves documentals de la lingua franca - Foltys, Christian (La Lingua franca : consideracions crítiques : traducció del document Proves documentals de la Lingua Franca, 2006)
Keywords: Linguistique

Sulayman al-Hilati, L’information historique et les structures du pouvoir ibadhite à Djerba - Merimi, Mohamed (Savoirs historiques au Maghreb: construction et usages, 2006)
Keywords: Ḥīlātī al-Ğarbī, Sulaymān ibn Aḥmad al- (16..-1688)

Libyens et Italiens en Tripolitaine (1911-1928) - Lahmar, Mouldi (Être notable au Maghreb, 2006)

Une famille maraboutique de Jerba au xviiie siècle - Merimi, Mohamed (Être notable au Maghreb, 2006)
Keywords: Monuments -- Djerba; Tâjdît, Mosquée (Fâtû, Djerba); Vie politique -- Djerba

Berber - Chaker, Salem; Mettouchi, Amina (Encyclopedia of Language & Linguistics, 2006)
Keywords: Linguistique